2000
DOI: 10.1053/he.2000.5978
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of alcohol dehydrogenase in europeans: The ADH2*2 allele decreases the risk for alcoholism and is associated with ADH3*1

Abstract: Polymorphism at the ADH2 and ADH3 loci of alcohol dehydrogenase (ADH) has been shown to have an effect on the predisposition to alcoholism in Asian individuals. However, the results are not conclusive for white individuals. We have analyzed the ADH genotype of 876 white individuals from Spain (n ‫؍‬ 251), France (n ‫؍‬ 160), Germany (n ‫؍‬ 184), Sweden (n ‫؍‬ 88), and Poland (n ‫؍‬ 193). Peripheral blood samples from healthy controls and groups of patients with viral cirrhosis and alcohol-induced cirrhosis, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
165
8
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(202 citation statements)
references
References 56 publications
24
165
8
5
Order By: Relevance
“…Since we, like others (Gilder et al, 1993;Whitfield et al, 1998;Borras et al, 2000), observed no association between ADH2 polymorphism and alcohol consumption in women without breast cancer, we could assess the interaction between these factors and risk for breast cancer using the case-only analysis, which is more powerful to detect gene-environment interactions than a case -control study (Piegorsch et al, 1994). In contrast to a case -control analysis, our analytic strategy has also the advantage of assessing associations independently in women with identical data collection procedures (i.e.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Since we, like others (Gilder et al, 1993;Whitfield et al, 1998;Borras et al, 2000), observed no association between ADH2 polymorphism and alcohol consumption in women without breast cancer, we could assess the interaction between these factors and risk for breast cancer using the case-only analysis, which is more powerful to detect gene-environment interactions than a case -control study (Piegorsch et al, 1994). In contrast to a case -control analysis, our analytic strategy has also the advantage of assessing associations independently in women with identical data collection procedures (i.e.…”
Section: Discussionmentioning
confidence: 74%
“…In particular, the observed risk and interaction may not be entirely due to the ADH2 polymorphism itself, but also to the linkage of ADH2 with other genes that are associated with an increased risk for breast cancer. ADH2 has been observed to be linked to ADH3 (Borras et al, 2000) and the ADH3*1 genotype was observed to be a risk factor for breast cancer in premenopausal women (Freudenheim et al, 1999). However, given the stronger metabolic effects of ADH2, the ADH3 -breast cancer association might also be confounded by ADH2.…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratio of hospitalization for alcoholism in men and women with the slow alcohol degradation ADH1B Á 1/1 genotype was 3.9 (95% CI: 1.0-16) and 2.7 (95% CI: 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…However, since ADH1B genotype and alcohol intake are not independent in our study population, the modifying effect of the ADH1B genotype on breast cancer risk associated with alcohol consumption is overestimated in the case-only analysis, partly due to residual confounding by differences in alcohol consumption caused by the genotype (Albert et al, 2001). Indeed, indications for an association between ADH1B genotype and alcohol consumption, alcoholism or ADH1B genotype, alcohol and breast cancer C Lilla et al adverse reactions such as flushing were observed in previous studies (Whitfield et al, 1998;Borras et al, 2000;Loew et al, 2003;Neumark et al, 2004). There is still controversy in the literature regarding the effect of ADH1B genotype on alcohol pharmacokinetics in vivo.…”
Section: Discussionmentioning
confidence: 99%